Get the answers you've been looking for with the help of IDNLearn.com's expert community. Get the information you need from our community of experts, who provide detailed and trustworthy answers.
Sagot :
Let's solve the equation [tex]\( -\frac{1}{5} n + 7 = 2 \)[/tex] step by step to find the value of [tex]\( n \)[/tex].
1. Isolate the term with [tex]\( n \)[/tex] on one side:
[tex]\[ -\frac{1}{5} n + 7 = 2 \][/tex]
Subtract 7 from both sides:
[tex]\[ -\frac{1}{5} n + 7 - 7 = 2 - 7 \][/tex]
Simplifying, we get:
[tex]\[ -\frac{1}{5} n = -5 \][/tex]
2. Solve for [tex]\( n \)[/tex]:
To isolate [tex]\( n \)[/tex], multiply both sides by [tex]\(-5\)[/tex]:
[tex]\[ (\frac{-1}{5} n) \times (-5) = -5 \times (-5) \][/tex]
Simplifying this, we get:
[tex]\[ n = 25 \][/tex]
Therefore, the value of [tex]\( n \)[/tex] that makes the equation true is:
[tex]\[ n = 25 \][/tex]
1. Isolate the term with [tex]\( n \)[/tex] on one side:
[tex]\[ -\frac{1}{5} n + 7 = 2 \][/tex]
Subtract 7 from both sides:
[tex]\[ -\frac{1}{5} n + 7 - 7 = 2 - 7 \][/tex]
Simplifying, we get:
[tex]\[ -\frac{1}{5} n = -5 \][/tex]
2. Solve for [tex]\( n \)[/tex]:
To isolate [tex]\( n \)[/tex], multiply both sides by [tex]\(-5\)[/tex]:
[tex]\[ (\frac{-1}{5} n) \times (-5) = -5 \times (-5) \][/tex]
Simplifying this, we get:
[tex]\[ n = 25 \][/tex]
Therefore, the value of [tex]\( n \)[/tex] that makes the equation true is:
[tex]\[ n = 25 \][/tex]
Thank you for being part of this discussion. Keep exploring, asking questions, and sharing your insights with the community. Together, we can find the best solutions. IDNLearn.com is your go-to source for dependable answers. Thank you for visiting, and we hope to assist you again.